Migrating motherhood and gendering exile: Eastern European women narrate migrancy and homing. (September 2015) - Christou, Anastasia; Michail, Domna
Synopsis: This article draws on a larger oral history project with Albanian, Bulgarian, Romanian and Polish migrant women living Greece, exploring how migrancy, motherhood and mothering intersect with how a negotiation and translation of emotional, cultural, embodied agency is transformed in the meanings of citizenship on translocal and transnational levels. We unpack gendered representations of how striving to belong is transmitted in migrant mothering practices and how the latter intersect with wider issues of immigration policy and status in an era of crises in Greece. In mapping experiences of migrant mothering through participant narratives, we demonstrate the importance of understanding mothering and migrancy as parallel, complementary and complex performativities. As such they form iconographies of resilience, incorporation and individual agency as women cope with being both migrants and mothers, often without extensive networks of support, and within a context of a wider xenophobic and crisis-ridden Greece.